CHARGE syndrome gastrointestinal involvement: from mouth to anus. Issue 1 (2nd February 2017) - Hudson, A.; Macdonald, M.; Friedman, J.N.; Blake, K.
Abstract : CHARGE syndrome is an autosomal dominant disorder that occurs as a result of a heterozygous loss‐of‐function mutation in the chromodomain helicase DNA‐binding ( CHD7 ) gene, which is important for neural crest cell formation. Gastrointestinal (GI) symptoms and feeding difficulties are highly prevalent but are often a neglected area of diagnosis, treatment, and research. Cranial nerve dysfunction, craniofacial abnormalities, and other physical manifestations of this syndrome lead to gut dysmotility, sensory impairment, and oral–motor function abnormalities. Over 90% of children need tube feeding early in their life and many experience weak sucking/chewing, gastroesophageal reflux disease (GERD), and aspiration. The mainstay of treatment thus far has consisted of feeding therapy, GERD medications, Nissen fundoplication, gastrostomy/jejunostomy, and food texture limitation. Owing to the multitude of severe medical issues associated with this genetic disorder, GI involvement is often overlooked. Here, we report on five patients with CHARGE syndrome who manifested a range of severe GI and feeding difficulties. Abstract : A review of the common gastrointestinal and feeding difficulties in CHARGE syndrome.